Species diversity of critically endangered pristid sawfishes (Elasmobranchii: Pristidae) Elasmobranchii: Pristidae (Malay Archipelago) - SUTARNO SUTARNO; AHMAD SETYAWAN; IWAN SUYATNA (Society for Indonesian Biodiversity, 2012)
Sutarno, Setyawan AD, Suyatna I. 2012. Species diversity of critically endangered pristid sawfishes (Elasmobranchii: Pristidae) Elasmobranchii: Pristidae (Malay Archipelago). Biodiversitas 13: 161-171. The pristid sawfishes (Pristidae) are notable because of their sawlike rostrum and large body size (up to seven meters). All pristids are listed as critically endangered by IUCN, since decreasingpopulation; Nusantara is home for five pristid species, namely: Anoxypristis cuspidata Latham, 1794, Pristis clavata Garman, 1906, Pristis microdon Latham, 1794, Pristis zijsron Bleeker, 1851, and Pristis pectinata Latham, 1794. A. cuspidata differ from Pristid spp. by the presence of a very narrow rostral saw, with 16 to 29 pairs of teeth except for the part along the quarter of the rostral saw near the head. P. microdon has a highly defined groove that runs along the entire posterior edge of the tooth into and beyond its confluence with the rostrum. This groove is absent in juvenile of P. clavata and whilst it develops in larger individuals it rarely runs along the entire posterior edge of the tooth or reach its confluence with the rostrum. P. clavata possibly have been misidentified as P. pectinata, whose distribution in the Indo-West Pacific is uncertain. P. clavata can be distinguished from P. pectinata and P. zijsron by the possession of fewer rostral teeth (18 to 22 in P. clavata cf. 24 to 28 in P. zijsron and 24 to 34 in P. pectinata), and by its smaller body size (i.e. less than 250 cm TL in P. clavata). P. microdon indicates different sexes of the number of rostral teeth, i.e. 17-21 in female cf. 19-23 in male, but in P. clavata, it can not be used to differentiate male from female, with both sexes possessing an average of 42 rostral teeth. In P. clavata the dorsal fin origin is opposite or slightly behind the pelvic fin origin, the rostum is relatively shorter (22-24% of TL), he lower cauda fin lobe is smaller.